R-curve behavior of laminated ZrB2-SiC/Graphite ceramics in two different directions. Issue 8 (1st June 2017) - Liu, Xinchao; Wei, Chuncheng; Feng, Liu; Niu, Jinye; Yang, Zanzhong
Abstract: Laminated ZrB2 -SiC/Graphite ceramics were fabricated by tap-casting and hot-pressing sintering. In this study, the R-curve behavior in two different directions was investigated using indentation-strength technique. The flexural strengths in the parallel direction and perpendicular direction were 382 MPa and 429 MPa, respectively. The indentation strength values first decreased and then increased with increasing the indentation load. When the indentation load was 294 N, the strength reached the maximum value of 360 MPa in the parallel direction and 399 MPa in the perpendicular direction. The laminated ZrB2 -SiC/Graphite ceramics exhibited an evident rising R-curve behavior in both directions, which was mainly attributed to the consumption of fracture energy by crack deflection and crack branching at the weak graphite layers.